Extreme value theory and copulas - Embrechts, Paul; Neslehova, Johanna (Henry Stewart Talks, 2007)
Extremes in quantitative risk management, Limiting behavior of sums and maxima, Fisher/Tippett theorem, Extreme value distributions and domains of attraction, Block maxima method, Threshold exceedances, Picands/Balkema/de Haan theorem, Threshold selection, Quantile estimation, Point process approach, Banking and insurance regulation, Critical appraisal
Archived at 2022/04/04